Serviço de acolhimento em família acolhedora e a (Des)institucionalização da primeira infância: família e condição humana - Sbaraglini, Geisa Araújo de Almeida (Universidade Federal de São Carlos, 2024)
This research is interdisciplinary in nature and deals with the Foster Care Service - SAF, with a focus on the (de)institutionalization of Early Childhood, Family and the Human Condition. The Family Reception Service is a protective, temporary, exceptional and preferential measure to Institutional Reception, provided for in the Child and Adolescent Statute – ECA, which aims to welcome children and adolescents in situations of social risk. The Foster Family, through provisional custody, assumes all care for the children and adolescents inherent to a family. The primary objective of the research is to understand the Foster Care Service and the Process of (De)Institutionalization of early childhood and its Human Condition. Starting from this objective, we are based on theorists who address the history of childhood Ariès (1978; 2022), Rizzini (2007), Freitas (2016); human condition, Arendt (2021), Butler (2015); social protection and families, Minayo (2016), Berberian (2013), Veronese (2021); and Family support, Cabral (2004), Fonseca (2006), Valente (2022). We carried out bibliographical research through the Capes theses and dissertations database, between 2017 and 2022, resulting in five master's dissertations, two in the area of social work, two in the area of law and one in the area of psychology, and research documentary, through Laws, Decrees and other official documents that deal with Family Accommodation. The reason for carrying out the study was after the death of a baby in the city of Bauru/SP, who was under protection measures in a Family Care Service and in view of this situation we sought to understand the Human Condition of children who were removed from family life. and the role of the Foster Family linked to the protection service. As a result, we consider that the Family Care Service is still relatively new and the practice of institutionalization remains present.Families need support from public policies that serve all members and stop being judged as incapable of providing care. We understand that the Family Care Service differs from institutional care, as the family that welcomes the child also welcomes their history and their family of origin, aiming to return the child to their family environment when appropriate. For these reasons, the results also indicate that the human condition of the child, which was previously deprived of protection, goes beyond its origins and today begins to be an expression of care and the Family Care Service, in turn, when welcoming early childhood, offers protection, individualized care, aiming at human development according to the child's peculiar condition. Finally, the aim is for the research to bring reflections on the different types of reception and their interdisciplinary complexities along with the network of services linked to high complexity and the articulation with the Special Social Protection Network determined by the Rights Guarantee System.
Fostering service in a foster family and (Des)Institutionalization from early childhood: family and the human condition
Keywords: Família Acolhedora; Infância; Condição Humana; Foster Family; Childhood; Human Condition; CIENCIAS HUMANAS; CIENCIAS SOCIAIS APLICADAS::SERVICO SOCIAL